DETERMINAN TINGKAT KEPATUHAN PENDERITA TB PARU BTA (+) DIWILAYAH KERJA DINAS KESEHATAN KOTA MEDAN TAHUN 2011 - erman suryadi; Heldy BZ; Fauzi . (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2012)
ABSTRACT Tuberculosis (TB) is an infectious disease caused by the bacteria Mycabacterium tuberculosis. Most of the TB germs attack the lungs, but can also on other organs. Treatment success largely depends on patient adherence to medication alloys. Achieving compliance is not easy for patients and healthcare provider, the majority of patients discontinued treatment before the end of the planned treatment or taking medication incorrectly. The experiment was conducted late May to July in 2012, using a qualitative approach. Information obtained through in-depth interviews with key informants, Drink Drugs Controller (PMO) and patients as well as observation. Analysis of the recorded information, record the tape recorder and analyzed manually, after which the matrix criteria, which were grouped according to research questions and objectives. The results showed symptoms experienced patients will be reduced after the intensive phase of treatment, after a phase of intensive supervision PMO to the patient start sagging so that patients do not follow the advanced stages of treatment. Lack of supervision by the officers of the PMO's role led task does not run well on the level of patient adherence to treatment through to completion. Based on the results of the study found that the main factors that cause TB patient drop-out region Medan City Health Office work is the behavior of the hospital, the patients themselves decide he is still healthy or sick. It is suggested that the TB control officer for more attention to the role and junctions of the PMO after the intensive phase of treatment. It is expected that the TB control officer for more foster ill behavior towards patients to better understand and appreciate that TB treatment should be finished with a time of 6-8 months. PMO is expected active so that patients seek treatment through to completion. Keywords: Determinants, Level Compliance, Pulmonary Tuberculosis